Conferences 2 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
ConferencesChemrawn XII - African food security and natural resource management: the new scientific frontiers20-24 June, 1999, KenyaAn international conference to foster stakeholder input to advance the role of chemistry and allied sciences in...